Proceedings of the ACM Symposium on Applied Perception 2012
DOI: 10.1145/2338676.2338688
|View full text |Cite
|
Sign up to set email alerts
|

Inferring artistic intention in comic art through viewer gaze

Abstract: Comics are a compelling, though complex, visual storytelling medium. Researchers are interested in the process of comic art creation to be able to automatically tell new stories, and also, summarize videos and catalog large collections of photographs for example. A primary organizing principle used by artists to lay out the components of comic art (panels, word bubbles, objects inside each panel) is to lead the viewer's attention along a deliberate visual route that reveals the narrative. If artists are succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Use of eyetracking data is consistent with other multimedia learning studies (e.g., [100]). Our study confirms prior comic eye-tracking studies [57,81] 21 two-part interviews were audio recorded and transcribed verbatim by the experimenter. Data was coded using the online data analysis application Dedoose [28].…”
Section: Interview and Eye-tracking Study Of The Password Comicsupporting
confidence: 84%
“…Use of eyetracking data is consistent with other multimedia learning studies (e.g., [100]). Our study confirms prior comic eye-tracking studies [57,81] 21 two-part interviews were audio recorded and transcribed verbatim by the experimenter. Data was coded using the online data analysis application Dedoose [28].…”
Section: Interview and Eye-tracking Study Of The Password Comicsupporting
confidence: 84%
“…Omori et al [2004] investigated factors that may guide eye movements during manga reading, and found that there is a strong link between eye movements and balloon positions. Jain et al [2012] experimentally confirmed that comic artists direct viewer attention through element composition, by measuring the consistency of eye movements across different viewers. However, none of these works present a model or algorithm for composing subjects and balloons.…”
Section: Related Workmentioning
confidence: 70%
“…We recorded the eye movements of 10 participants on the 11 pairs of compositions used in the visual perception study, with 5 on our results and another 5 on the results by the heuristic method. Following Jain et al [2012], we measure the consistency in both unordered and ordered eye fixations across different viewers.…”
Section: Comparison To Heuristic Methodsmentioning
confidence: 99%
“…Jain et al () compared the similarity of different viewers' scanpaths between comics, amateur snapshots, and robot pictures, finding the most coherent viewing behavior for comics. They conclude that artists are successful in guiding their readers' attention.…”
Section: Reading Of Comicsmentioning
confidence: 99%